Bird sound identification based on artificial neural network - Mohd Sukri, Muhammad Mujjajdid; Fadlilah, Umi; Saon, Sharifah; Mahamad, Abd Kadir; Md Som, Mohamad; Sidek, Azmi (2020)
Due to effect of climate changes and count of endangered animal, many researchers proposed animal species recognition system to help them for specific study. This paper proposes to identify bird sound identification using Artificial Neural Network (ANN). Each bird has a different tone of sounds. ANN is applied to classify and recognise the bird sounds using Matlab software. Firstly, all required data in term of power spectral density of bird is used in order to obtain data for each bird types. The next process is to train ANN to identify species of birds. Only one bird can identify in one time. Lastly, the graphical user interface (GUI) of bird sound identification have been developed that required the user to fed audio input of bird sound in order to recognise bird species. This project is done successfully and can be used to identify bird species.